Determinants of Stunting Among Children Under Five Years in Indonesia: Evidence from the 2021-2022 Demographic and Health Survey - Siregar, Rahmah Juliani; Harahap, Maryam Latifah; Suryani, Elvi (International Journal of Public Health Excellence (IJPHE), 2024)
At the global level, the prevention of stunting is one of the Sustainable Development Goals (SDGs). Indonesia is currently working towards achieving the second Sustainable Development Goal, which entails ending hunger, ensuring food security, improving nutrition, and supporting sustainable agriculture. As a part of this objective, efforts are being made to decrease the prevalence of stunting in children by 2025. Attention towards stunting is crucial as it can adversely affect children's physical and cognitive development well into adulthood if not addressed appropriately. This paper conducted a literature review from various sources, with a focus on google scholar and prioritizing sources from the last five years, as well as research on the population in Indonesia. It was determined through the analysis of several sources that maternal, child, and environmental factors pose various risks for stunting in Indonesia. Maternal factors that may play a role in child development include the mother's age, upper arm circumference, height, breastfeeding or complementary feeding practices, early initiation of breastfeeding and food quality during pregnancy. A history of low birth weight or prematurity, male sex, neonatal illness, frequent and recurrent diarrhea, infectious diseases, and lack of immunization are among the child factors associated with developmental outcomes. Factors such as living in a low socio-economic environment, limited family education, especially maternal education, insufficient household income, open defecation in rivers, gardens or inadequate latrines, consumption of untreated drinking water and high exposure to pesticides are also associated with the prevalence of stunting.